2023
DOI: 10.1111/mpp.13323
|View full text |Cite
|
Sign up to set email alerts
|

A salivary secretory protein from Riptortus pedestris facilitates pest infestation and soybean staygreen syndrome

Abstract: The bean bug (Riptortus pedestris), one of the most important pests of soybean, causes staygreen syndrome, delaying plant maturation and affecting pod development, resulting in severe crop yield loss. However, little is known about the underlying mechanism of this pest. In this study, we found that a salivary secretory protein, Rp614, induced cell death in nonhost Nicotiana benthamiana leaves. NbSGT1 and NbNDR1 are involved in Rp614‐induced cell death. Tissue specificity analysis showed that Rp614 is mainly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Rp614, originating from Riptortus pedestris (Hemiptera, Alydidae), serves as a pivotal inducer of cell death in nonhost Nicotiana benthamiana leaves, involving NbSGT1 and NbNDR1. Concurrently, it suppresses the soybean immune response during R. pedestris infestation by influencing the expression of hormonal defense genes, particularly those associated with SA and JA pathways [ 80 ]. Salivary proteins Bsp9 and Bt56 from B. tabaci modulate plant defense differently, with Bsp9 enhancing feeding on tomato plants by suppressing WRKY33 and MAP-kinase interactions, while Bt56 influences SA signaling in tobacco through the regulation of a KNOTTED1-like transcription factor [ 81 , 82 ].…”
Section: Effects Of Sps On Host Plantsmentioning
confidence: 99%
“…Rp614, originating from Riptortus pedestris (Hemiptera, Alydidae), serves as a pivotal inducer of cell death in nonhost Nicotiana benthamiana leaves, involving NbSGT1 and NbNDR1. Concurrently, it suppresses the soybean immune response during R. pedestris infestation by influencing the expression of hormonal defense genes, particularly those associated with SA and JA pathways [ 80 ]. Salivary proteins Bsp9 and Bt56 from B. tabaci modulate plant defense differently, with Bsp9 enhancing feeding on tomato plants by suppressing WRKY33 and MAP-kinase interactions, while Bt56 influences SA signaling in tobacco through the regulation of a KNOTTED1-like transcription factor [ 81 , 82 ].…”
Section: Effects Of Sps On Host Plantsmentioning
confidence: 99%
“…In recent years, the soybean plants of a large area in the Huang-Huai-Hai region of China have presented stay-green syndrome (known as the "Zhengqing" problem in Chinese), with delayed leaf senescence (stay-green), flat pods, and aborted seeds, causing significant economic losses [10][11][12]. At least three types of causal factors associated with stay-green syndrome have been discovered to date: the bean stinkbug Riptortus pedestris (Fabricius) (Hemiptera: Alydidae), which pierces and sucks soybean pods at the R 3 -R 5 stages (from the beginning of pod development to the beginning of seed development) [13,14]; the novel soybean stay-green-associated geminivirus (SoSGV) [15][16][17]; and the virus-transmitting leafhopper, Orosius orientalis (Matsumura) (Hemiptera: Cicadellidae) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Riptortus pedestris (Hemiptera: Coreidae) is an important agricultural pest with a wide geographical distribution, mainly in Asia, including China, South Korea, Japan, and India [20][21][22]. Recently, more attention has been paid to this pest, as field and laboratory experiments revealed that R. pedestris may be the main cause of soybean Zhengqing [22][23][24][25]. Zhengqing disease is a staygreen syndrome in soybeans that causes large soybean yield losses in northern China [22,26].…”
Section: Introductionmentioning
confidence: 99%